The long-term effect of migration on economic inequality between EU Member States - Magdalena Ulceluse (Global Labor Organization (GLO), 2019)
This paper explores the long-term effect of migration on economic inequality between the 28 EU member states, covering the period 1995-2017. The cross-national, longitudinal analysis demonstrates that migration has had a positive and significant effect on development and economic growth in 28 member states. However, the findings also indicate that some countries have benefitted from migration more than others. Specifically, for countries experiencing positive net migration the effect is disproportionately larger than for countries experiencing negative net migration. This seems to indicate that, while migration has indeed contributed to economic development in all member states over the period analysed, it has not necessarily contributed to decreasing economic inequalities between them.
Keywords: F220; O150; O47; 330; immigration; emigration; inequality; migration and development; EU